1999
DOI: 10.1111/j.1532-5415.1999.tb02991.x
|View full text |Cite
|
Sign up to set email alerts
|

Management and Outcome of Acute Myocardial Infarction in Older Patients in the Thrombolytic Era

Abstract: Patients more than age 75 comprise almost one-third of patients with AMI and have a poor prognosis. Although age is an independent predictor of mortality following AMI, suboptimal management may contribute to the high mortality in these patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
5
1

Year Published

2000
2000
2008
2008

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 38 publications
2
5
1
Order By: Relevance
“…In the year 2000, the benefit of thrombolysis was questioned by Thiemann et al, who even suggested a survival disadvantage in elderly patients [12]. Thoughts along this line might explain why many older patients with ST-segment elevation ACS worldwide remain untreated [11,26]. Our figures indicate that this was also the case among our patients, although PCI rather than thrombolysis was underused in comparison with the younger age groups, among both women and men.…”
Section: Findings In Relation To Agecontrasting
confidence: 38%
See 3 more Smart Citations
“…In the year 2000, the benefit of thrombolysis was questioned by Thiemann et al, who even suggested a survival disadvantage in elderly patients [12]. Thoughts along this line might explain why many older patients with ST-segment elevation ACS worldwide remain untreated [11,26]. Our figures indicate that this was also the case among our patients, although PCI rather than thrombolysis was underused in comparison with the younger age groups, among both women and men.…”
Section: Findings In Relation To Agecontrasting
confidence: 38%
“…Greater comorbidity might explain the less frequent use of invasive procedures in elderly patients. A number of reports have demonstrated that older patients with an acute MI often have a more complicated hospital course than younger ones [11]. In our study, the occurrence of re-infarction, heart failure and atrial fibrillation increased with age, as did the use of inotropic drugs, anti-arrhythmics and diuretics.…”
Section: Findings In Relation To Agementioning
confidence: 50%
See 2 more Smart Citations
“…Age is an independent predictor of mortality after acute myocardial infarction, which makes the elderly patients a high-risk group for complications and mortality 24,25 . Therefore, they have the highest potential for therapeutic benefit resulting from the use of medication that has been proved to reduce mortality after acute myocardial infarction, such as beta-blockers, acetylsalicylic acid, and angiotensin-converting enzyme inhibitors.…”
Section: Discussionmentioning
confidence: 99%